2015
DOI: 10.1016/j.jimonfin.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Democracy, political risks and stock market performance

Abstract: This study examines the impacts of democracy and political risk on stock market. Using annualized panel data for 49 emerging markets for 2000-2012 we find evidence that democracy and political risk do have impact on stock market returns and the relationship between democracy and political risk is parabolic i.e., there is a threshold level of democracy after which political risk begins to decline. Our also results suggest that decreases in political risk lead to higher returns.JEL classification: G15, G12, F52

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 50 publications
12
81
1
4
Order By: Relevance
“…8, No. 7; F test, at a degree of freedom 2 and level of significance 0.05, revealed that average daily return on EGX30 did not respond to changes in the level of political risk, which goes in line with the finding of Lehkonen and Heimonen (2015), as their study indicated that the effect of political risk on stock returns fades gradually.…”
Section: Examine the Variation And Homogeneity Of Average Daily Retursupporting
confidence: 57%
“…8, No. 7; F test, at a degree of freedom 2 and level of significance 0.05, revealed that average daily return on EGX30 did not respond to changes in the level of political risk, which goes in line with the finding of Lehkonen and Heimonen (2015), as their study indicated that the effect of political risk on stock returns fades gradually.…”
Section: Examine the Variation And Homogeneity Of Average Daily Retursupporting
confidence: 57%
“…It is noteworthy that there is another strand of interesting research on political elections, stock market volatility, and stock market performance (see among others, Bialkowski et al 2008; Goodell and Vähämaa 2013; Johnson et al 1999; Kirui et al 2014; Kabiru et al 2015; Lehkonen and Heimonen 2015; Li and Born 2006; Opare 2012; Smales 2014, 2015, 2016). In particular, Bialkowski et al (2008) found evidence that stock market volatility is substantially raised around national elections over 27 industrialised nations.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Lehkonen and Heimonen (2015) provided evidence that political uncertainty had significant impact on stock market performance of 49 emerging markets.…”
Section: Introductionmentioning
confidence: 99%
“…This may sound contradictory to the current analysis on such occasions in the Middle East. [135][136][137] However, what we mean here is that in many cases, activities such as mass protests increase the°ow of opportunities and increase fairness, when those are evaluated by the authorities as the wills of the society for more freedom, and better and fairer rules and regulations rather than mere acts of the chronic opponents of the governors. So, such protests are the means to ask for fairer systems but they do not provide any guarantee for fairer systems by themselves.…”
Section: In Particularmentioning
confidence: 99%